Screen to Succeed: Exploring the Influence of Videos on Young Learners’ English Acquisition - Stefany Candelero Chable; Cruz Martínez Cruz Martínez (Enletawa Journal)
This research attempts to show how videos influence on young learners’ language development because of the constant use of technology nowadays. It seeks to understand the impact of videos on young learners learning English as a foreign language in school. By means of a qualitative approach, a case study was conducted using participant and structured observation on 7 children in preschool 1. The data were analyzed by means of thematic analysis. The findings shed light on the impact of videos on physical and verbal reactions, promoting interest and participation. They also show how the videos help children to acquire new vocabulary and how they should be used for effective pedagogical implementation. Videos positively impact on EFL teaching, providing enjoyable learning for young learners and giving teachers more classroom tools.